Penerapan Diversi Berdasarkan Pasal 6 dan 7 Undang-Undang Nomor 11 Tahun 2012 tentang Sistem Peradilan Anak Perspektif Hukum Pidana Islam - Aldi Bahtiar; Deden Najmudin; Didi Sumardi (PESHUM : Jurnal Pendidikan, Sosial dan Humaniora, 2026)
The implementation of diversion under Law Number 11 of 2012 concerning the Juvenile Criminal Justice System (UU SPPA), particularly Articles 6 and 7, faces a gap between its normative restorative ideals and practical enforcement. Meanwhile, the perspective of Islamic criminal law, through the concepts of taklīf and tamyīz, offers a more precise gradation of children’s criminal responsibility. This study addresses the gap in integrative analysis between these two legal systems in order to achieve substantive justice for children in conflict with the law. This research employs a normative juridical approach with comparative analysis, utilizing primary data (the UU SPPA, Supreme Court Regulation No. 4 of 2014, and 15 court decisions from 2020–2025) and secondary data (fiqh jināyah literature and reports from ICJR and KPAI). The analysis is qualitative, descriptive-analytical in nature, applying statute, case, and conceptual approaches to compare positive legal norms with the principles of maṣlaḥah and ta’dīb. The provisions of Articles 6 and 7 have been effective in reducing recidivism by 25% and shortening detention periods, aligning with the Islamic concept of ta’dībiyyah for mumayyiz children. However, implementation remains constrained by formalistic practices within correctional institutions (Bapas) and resistance from victims. A strong correlation with the concept of ṣulḥ (Qur’an 49:9–10) produces a more holistic form of justice, although the statutory age gradation remains less flexible compared to the doctrine of tamyīz. The synergy between the UU SPPA and Islamic criminal law thus generates an inclusive restorative juvenile justice model consistent with the objectives of maqāṣid al-sharī‘ah